Gendered Language Features in Facebook in Communication among Millennials in Malaysia - Fung, Kirstie Tet Mei (Universiti Malaysia Sarawak (UNIMAS), 2021)
This study was carried out with the aim of to analyse gendered language features found in Facebook comments made by Malaysian millennials. This scope of this study is confined to analysing Facebook comments and participants were selected among Malaysian millennials group. Gendered language features from Facebook comments that were written by Malaysian millennials were analysed using a framework of analysis of gendered language features. Subsequently, an online questionnaire participated by 60 participants was also carried out as part of data triangulation. From the 260 comments collected, it was revealed that most comments had male language features. The analysis of the online questionnaires provided several reasons when identifying a commenter’s gender. A comparison between the analysis of the Facebook comments and answers from the questionnaire was carried out to investigate whether or not language features found online reflect normal face-to-face communication. The findings reveal that gender language patterns have differed from the conventional norms, especially when some comments were reported to have cross gender language patterns. The also implies that gender language patterns used among the Malaysian millennial age group have blurred, thus changing how conventional language norms are used when interacting online.